2023
DOI: 10.1007/s12072-022-10480-y
|View full text |Cite
|
Sign up to set email alerts
|

Real-world efficacy and prognostic factors of lenvatinib plus PD-1 inhibitors in 378 unresectable hepatocellular carcinoma patients

Abstract: Introduction Combining lenvatinib with a programmed cell death protein-1 (PD-1) inhibitor has been explored for the treatment of un-resectable hepatocellular carcinoma (uHCC). This study aimed to investigate the real-world efficacy of and prognostic factors for survival associated with lenvatinib plus PD-1 inhibitor treatment in a large cohort of Asian uHCC patients even the global LEAP-002 study failed to achieve the primary endpoints. Methods Patients wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 48 publications
3
19
2
Order By: Relevance
“…Further, lenvatinib monotherapy seemed to be stronger than the other control arms with sorafenib in terms of OS (19.0 months for lenvatinib vs. 13.4–15.5 months for sorafenib) as well as ORR (17.5% for lenvatinib vs. 5.1–11% for sorafenib). These encouraging data of the combination of lenvatinib plus PD-1 inhibitors were found as well in real-world setting of a HCC Chinese population harboring a heterogeneity in general status (ECOG PS 0 to 2) and liver functions (Child-Pugh A and B) ( 16 ). Globally, OS was 17.8 months (95% CI: 14.0–21.6) with ORR at 19.6% (95% CI: 15.6–23.6%).…”
Section: Role Of Lenvatinib In Systemic Therapy For Hepatocellular Ca...supporting
confidence: 52%
See 1 more Smart Citation
“…Further, lenvatinib monotherapy seemed to be stronger than the other control arms with sorafenib in terms of OS (19.0 months for lenvatinib vs. 13.4–15.5 months for sorafenib) as well as ORR (17.5% for lenvatinib vs. 5.1–11% for sorafenib). These encouraging data of the combination of lenvatinib plus PD-1 inhibitors were found as well in real-world setting of a HCC Chinese population harboring a heterogeneity in general status (ECOG PS 0 to 2) and liver functions (Child-Pugh A and B) ( 16 ). Globally, OS was 17.8 months (95% CI: 14.0–21.6) with ORR at 19.6% (95% CI: 15.6–23.6%).…”
Section: Role Of Lenvatinib In Systemic Therapy For Hepatocellular Ca...supporting
confidence: 52%
“…In real-world setting from a Chinese population of 378 patients treated by lenvatinib plus PD-1 inhibitors, data were quite similar, showing 57.9% TRAE of grade 3–4, but higher rate of treatment discontinuation (24.6%). The most frequent grade 3–4 TRAEs were arterial hypertension (15.1%), increased blood bilirubin levels (8.5%), fatigue (7.7%), proteinuria (7.1%), decreased platelet count (6.9%), decreased appetite (6.3%), hypokalemia (6.3%), and diarrhea (5.8%) ( 16 ).…”
Section: Role Of Lenvatinib In Systemic Therapy For Hepatocellular Ca...mentioning
confidence: 99%
“…Lenvatinib-based combination therapy is the most common selection, which has been proved to provide inspiring tumor control and survival benefits for unresectable or advanced HCC. 27,28 Considering the increased applications of hepatic arterial chemotherapy (HAIC) in advanced HCC, this study aimed to investigate the efficacy and safety of HAIC added to the Lenvatinib-ICIs therapy, anticipating achieving superior oncological outcomes. For unresectable HCC, the combination of lenvatinib and pembrolizumab achieved an ORR of 46.0% in a Phase IB study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the current guidelines recommend “A + T” or durvalumab plus tremelimumab (D + T) as first‐line systemic therapies for TACE‐refractory or advanced HCC, only a small proportion of patients in our clinical practice choose the above regimens mainly due to financial burdens. Lenvatinib‐based combination therapy is the most common selection, which has been proved to provide inspiring tumor control and survival benefits for unresectable or advanced HCC 27,28 . Considering the increased applications of hepatic arterial chemotherapy (HAIC) in advanced HCC, this study aimed to investigate the efficacy and safety of HAIC added to the Lenvatinib‐ICIs therapy, anticipating achieving superior oncological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The phase III LEAP-002 study, which compared the combination of lenvatinib and pembrolizumab with the combination of lenvatinib and placebo as first-line treatment for advanced unresectable hepatocellular carcinoma, did not meet the primary endpoints of overall survival (OS) and progression-free survival (PFS) [ 17 ]. A result from a large-scale real-world study showed that there was no significant difference in OS between the combination of lenvatinib and pembrolizumab and the combination of lenvatinib with other programmed cell death protein 1 (PD-1) inhibitors [ 18 ].…”
Section: Introductionmentioning
confidence: 99%